If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + -4)(7x + 5) = 0 Reorder the terms: (-4 + 7x)(7x + 5) = 0 Reorder the terms: (-4 + 7x)(5 + 7x) = 0 Multiply (-4 + 7x) * (5 + 7x) (-4(5 + 7x) + 7x * (5 + 7x)) = 0 ((5 * -4 + 7x * -4) + 7x * (5 + 7x)) = 0 ((-20 + -28x) + 7x * (5 + 7x)) = 0 (-20 + -28x + (5 * 7x + 7x * 7x)) = 0 (-20 + -28x + (35x + 49x2)) = 0 Combine like terms: -28x + 35x = 7x (-20 + 7x + 49x2) = 0 Solving -20 + 7x + 49x2 = 0 Solving for variable 'x'. Factor a trinomial. (-5 + -7x)(4 + -7x) = 0Subproblem 1
Set the factor '(-5 + -7x)' equal to zero and attempt to solve: Simplifying -5 + -7x = 0 Solving -5 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -7x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -7x = 0 + 5 -7x = 0 + 5 Combine like terms: 0 + 5 = 5 -7x = 5 Divide each side by '-7'. x = -0.7142857143 Simplifying x = -0.7142857143Subproblem 2
Set the factor '(4 + -7x)' equal to zero and attempt to solve: Simplifying 4 + -7x = 0 Solving 4 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -7x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -7x = 0 + -4 -7x = 0 + -4 Combine like terms: 0 + -4 = -4 -7x = -4 Divide each side by '-7'. x = 0.5714285714 Simplifying x = 0.5714285714Solution
x = {-0.7142857143, 0.5714285714}
| 3v+w+8-2v+2= | | -2-17-22=2y+3(y-6) | | -5+(19)+(-34)+44= | | 2x+5x^4+6=0 | | 8(4x+4)= | | -6(x+3)+2x+6=8x+7 | | 20*7-4*7= | | -16t^2+144t-160=0 | | 15w+21=3(5w-7) | | -5+200=100 | | 3y^2-6y-24= | | -3+3(z-2)=(-7z+3)-6 | | 3x=cos(0.5x) | | 18=6v | | 4u-7u=-1-14 | | 5(-3-6n)=195 | | 4x^2-4x-48= | | (x+4)(xy-6)=7x | | 16x^2+-40x+25=0 | | 5/2*4-10/5+6= | | 16x-40x+25=0 | | 5x^3-20x= | | -3y+2x-10y-5x+2y= | | 2(3ab+4bc+-2x)*x+-3x(2ab+-5cb+-4x+2)=0 | | 2f*f*3f= | | (7x^2-6x+29)+(2x^2+9x-72)= | | -3x+3y=18 | | 16/2*4-10/5+6= | | 6-17=-7y-4y | | 3x-4+5x=10x-(3+2x) | | 7+18=6u-u | | v^2-2v-3= |